Hereditary and Acquired Angioedema: Experience with Patients in Puerto Rico - Santaella, María L.; Martinó, Alejandro (Puerto Rico Health Sciences Journal, 2004)
Hereditary (HAE) and acquired (AAE) angioedema are vascular reactions involving the sub mucosal tissues, representing localized edema caused by dilatation and increased permeability of the capillaries. HAE and AAE are clinical disorders characterized by angioedema that require prompt differentiation from other causes of angioedema in order to receive the most pertinent and effective therapeutic interventions. The aim of this report is to describe the clinical characteristics of patients with both HAE and AAE identified and followed at the Immunology Clinic of the University Hospital at the Puerto Rico Medical Center, their response and side effects to danazol therapy and their comparison with other series of similar patients reported in the literature. Overall, the patients in this sample presented a similar clinical profile compared to other reported series in the literature.